COMPARISON BETWEEN GLYCOGEN LEVEL OF KIDNEY TUBULAR CELLS IN DIABETIC KIDNEY STONE PATIENTS AND NON DIABETIC KIDNEY STONE PATIENTS - Ramadhan, Ken; Sugandi, Suwandi; Noegroho, Bambang S; Tjahjodjati, Tjahjodjati; Safriadi, Ferry; Siregar, Safendra; Adriansjah, Ricky; Adi, Kuncoro; Sihombing, Aaron Tigor; Yusuf, Makmuri (Indonesian Urological Association, 2011)
Objective: To compare glycogen level of kidney tubular cells in diabetic kidney stone patients with nondiabetic kidney stone patients. Material & method: We reviewed kidney stone patients who underwent nephrectomy in Hasan Sadikin Hospital from February 2008 to January 2009. Age, gender, type of DM, and urine pH were recorded. Glycogen level of kidney tubular cells were evaluated histochemically using HE, PAS, and PAS diastase. The results were categorized into 3 grades, based on the staining appearance compared to liver cells as controls. The results of diabetic group were compared to non diabetic patients. Results: There were 30 patients eligible for this study, 15 in diabetic group and 15 non diabetic patients. In the diabetic group, there were 10 patients with urine pH < 6 and 5 patients with a pH of 6,5. In the non diabetic group all urine pH were > 6,5. Examination revealed that glycogen level of kidney tubular cells in diabetic group was higher than in non diabetic group. Conclusion: Glycogen level of kidney tubular cells in diabetic kidney stone patients was higher than in non diabetic kidney stone patients. Keywords: Tubular cell, kidney stone, diabetes mellitus.